Effects of Verbal Priming With Acute Exercise on Convergent Creativity. Issue 1 (February 2022) - Frith, Emily; Miller, Stephanie E.; Loprinzi, Paul D.
The acute effects of moderate-intensity treadmill exercise during anagram problem solving on subsequent creativity performance has yet to be empirically investigated, which was this study's purpose. A two-visit (counterbalanced order), within-subject experiment was conducted among individuals aged 18–35. For the acute exercise visit, participants engaged in a 15-minute bout of moderate-intensity treadmill exercise while solving anagram problems. For the anagram only visit, participants engaged in 15 minutes of seated rest while solving anagram problems. Average RAT performance was higher for the exercise + anagram problem-solving visit ( M  = 10.51, SD = 3.25) compared to anagram-solving + seated rest ( M  = 9.29, SD = 4.12). The difference between conditions was statistically significant, t (44) = 2.385, p  = .021, Cohen's d  = 0.36. These findings demonstrate that acute exercise coupled with anagram problem-solving, prior to RAT completion, is a potential strategy for enhancing verbal convergent creative thinking.